Intervención cognitivo-conductual grupal para pérdida de peso y calidad de vida en pacientes candidatos a cirugía bariátrica (2014)
Obesity is a global health problem associated with the development of chronic degenerative diseases. Bariatric surgery has proven to be the most effective treatment for severe obesity. Despite surgery, patients must change their lifestyle in order to maintain weight loss in the long term. It has been reported that cognitive behavioral interventions have been effective to promote a lifestyle change and weight loss in obese patients. The aim of this study was to assess the effectiveness of a cognitive behavioral group intervention on weight loss and quality of life before surgery. Participants were nine morbidly obese patients, without psychiatric comorbidities, candidates for bariatric surgery. An initial assessment of quality of life that measured weight and BMI (Body Mass Index, for its English acronym) was performed. Patients underwent a group intervention in order to promote weight loss through cognitive behavioral techniques. The average weight loss was 5.7 kg during the five weeks of treatment, showing statistical significance of .001. In turn, along with weight loss, there was a decrease in BMI, with a statistical significance of .002. Regarding quality of life, there was significant improvement in body perception and attitude toward treatment.